Antibiotic-Resistant Bacteremia in Young Children Hospitalized With Pneumonia in Bangladesh Is Associated With a High Mortality Rate. (15th July 2021) - Chisti, Mohammod Jobayer; Harris, Jason B; Carroll, Ryan W; Shahunja, K M; Shahid, Abu S M S B; Moschovis, Peter P; Schenkel, Sara R; Hasibur Rahman, Abu Sayem Mirza Md; Shahrin, Lubaba; Faruk, Tanveer; Kabir, Farhad; Ahmed, Dilruba; et al.
Abstract: Background: Pneumonia is a leading cause of sepsis and mortality in children under 5 years. However, our understanding of the causes of bacteremia in children with pneumonia is limited. Methods: We characterized risk factors for bacteremia and death in a cohort of children admitted to the Dhaka Hospital of the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr, b) between 2014 and 2017 with radiographically confirmed pneumonia. Results: A total of 4007 young children were hospitalized with pneumonia over the study period. A total of 1814 (45%) had blood cultures obtained. Of those, 108 (6%) were positive. Gram-negative pathogens predominated, accounting for 83 (77%) of positive cultures. These included Pseudomonas (N = 22), Escherichia coli (N = 17), Salmonella enterica (N = 14, including 11 Salmonella Typhi), and Klebsiella pneumoniae (N = 11). Gram-positive pathogens included Pneumococcus (N = 7) and Staphylococcus aureus (N = 6). Resistance to all routinely used empiric antibiotics (ampicillin, gentamicin, ciprofloxacin, and ceftriaxone) for children with pneumonia at the icddr, b was observed in 20 of the 108 isolates. Thirty-one of 108 (29%) children with bacteremia died, compared to 124 of 1706 (7%) who underwent culture without bacteremia (odds ratio [OR], 5.1; 95% confidence interval [CI], 3.3–8.1; P  < .001). Children infected with bacteria resistant to all routinely used empiric antibiotics were at greater risk of death compared to children without bacteremia (OR, 17.3; 95% CI, 7.0–43.1; P  < .001). Conclusions: Antibiotic-resistant Gram-negative bacteremia in young children with pneumonia in Dhaka, Bangladesh was associated with a high mortality rate. The pandemic of antibiotic resistance is shortening the lives of young children in Bangladesh, and new approaches to prevent and treat these infections are desperately needed. Abstract : A large portion of children with pneumonia and bacteremia in Bangladesh harbored antibiotic-resistant Gram-negative pathogens. The risk of death was associated with increasing antibiotic resistance. The findings are an indication of the consequences of the pandemic of antibiotic resistance.